Efficacy of catuama® and low-level laser therapy in the treatment of burning mouth syndrome: a literature review (Research, Society and Development, 2022)
Burning mouth syndrome (BMS) is a condition of multifactorial origin whose etiology of the disease process is unknown, but it is believed to be of neuropathic origin. The literature has evaluated the effectiveness of various forms of treatment for BMS, whether with drugs or non-pharmacological therapies. Within the group of pharmacological therapies, there is an emerging phytopharmaceutical that has been demonstrating desirable effects in the treatment of BMS, catuama®, among the non-pharmacological therapies, the one that stands out is the low-level laser therapy (LLLT). Thus, the present study aimed to carry out a literature review about the therapeutic potential of catuama® and TLBI in the treatment of BMS. This study is a narrative literature review, in which the following databases were consulted: Virtual Health Library (VHL), Medical Publications (PubMed), Google Scholar, Medline and the Scientific Electronic Library virtual library Online (SCIELO). To carry out this search, the Descriptors in Health Science (DECS) were used: Burning Mouth Syndrome, Low-Level Light Therapy and Phytotherapy, alone and together, thus, according to the established inclusion and exclusion criteria, 22 references were selected for carrying out this review. This study shows that the literature supports both catuama® and LLLT as good therapeutic measures in the treatment of BMS, however, clinical trials need to be carried out in order to standardize a safe and practical protocol for the use of these therapies in the treatment of this condition.